A rare presentation of primary cardiac myxofibrosarcoma: Case report and literature review - Sepideh Soltani; Maryam Garousi; Elahe Mirzaee; Sogol Koolaji; Hengameh Nazari; Sepideh Emami; Ali Zare Mehrjardi; Amir Mohammad Arefpour (Cancer Reports, 2024)
Abstract Background Primary cardiac myxofibrosarcoma is a rare and aggressive malignancy, with the majority of approaching strategies relying on case reports. This article provides insights into its diagnosis and treatment. Case Presentation This paper presents the case of a 40‐year‐old man with sudden onset hemoptysis, leading to the diagnosis of primary cardiac myxofibrosarcoma. Treatment involved open‐heart surgery to excise the left atrium tumor, followed by 6 cycles of adjuvant chemotherapy. Unfortunately, brain metastasis developed, leading to the patient's death 1 year after initial diagnosis. Conclusion Primary cardiac myxofibrosarcoma remains a clinical challenge with an unfavorable prognosis. Early diagnosis through advanced imaging is crucial, and research is needed to explore innovative treatments. This case underscores the complexities of managing this rare cardiac malignancy and highlights the necessity for ongoing investigations to enhance patient outcomes.